2011
DOI: 10.1111/j.1600-0625.2011.01272.x
|View full text |Cite
|
Sign up to set email alerts
|

PTPN22 1858T is not a risk factor for North American Pemphigus vulgaris

Abstract: Alterations in the protein tyrosine phosphatase N22 (PTPN22) gene affect the threshold for lymphocyte activation. The PTPN22 1858T polymorphism leads to uninhibited T-cell receptor cascade propagation. An elevated PTPN22 1858C/T genotype frequency has been correlated with several autoimmune disorders which have T-cell and humoral components. However, a recent Tunisian report demonstrated no association between PTPN22 1858T and patients with Pemphigus vulgaris (PV), an autoantibody-associated blistering disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 44 publications
(67 reference statements)
1
8
0
3
Order By: Relevance
“…103 PV is caused by antibodies against desmoglein 1 or desmoglein 3, resulting in the loss of cohesion between keratinocytes and subsequent skin blisters. 135 In 2011, Sachdevet et al 64 reported no association between PTPN22 C1858T and PV, confirming a previous observation in a Tunisian population. 136 A strong association between PTPN22 C1858T and two other autoimmune diseases has been reported.…”
Section: Diseases Showing No or Weak Association With Ptpn22supporting
confidence: 73%
See 2 more Smart Citations
“…103 PV is caused by antibodies against desmoglein 1 or desmoglein 3, resulting in the loss of cohesion between keratinocytes and subsequent skin blisters. 135 In 2011, Sachdevet et al 64 reported no association between PTPN22 C1858T and PV, confirming a previous observation in a Tunisian population. 136 A strong association between PTPN22 C1858T and two other autoimmune diseases has been reported.…”
Section: Diseases Showing No or Weak Association With Ptpn22supporting
confidence: 73%
“…Association between PTPN22 and other autoimmune diseases Besides the autoimmune diseases mentioned above, an association between PTPN22 and several other autoimmune diseases has been investigated, including ankylosing spondylitis (AS), primary sclerosing cholangitis (PSC), primary biliary cirrhosis (PBC), idiopathic inflammatory myopathies (IIM), acute anterior uveitis (AAU), immune thrombocytopenia and pemphigus vulgaris (PV). 64,103,[127][128][129][130][131] The results are summarized in Supplementary Table S1. Only one case-control study was conducted for each disease in European populations or populations of European descent, making meta-analysis impossible.…”
Section: Diseases Showing No or Weak Association With Ptpn22mentioning
confidence: 99%
See 1 more Smart Citation
“…Different HLA alleles have been reported in different populations, highlighting common HLA class II subtypes (especially between DR and DQ) in different ethnic groups. Currently, few non-HLA genes have been definitively linked to PV (Gazit et al, 2004;Javor et al, 2010;Sachdev et al, 2011;Tanasilovic et al, 2017); only a handful of studies on a limited number of genes in PV have been performed. The genome-wide association studies (GWASs) of PV in the Jewish population not only highlighted the role of HLA in the pathogenesis of PV but also identified the populationspecific non-HLA gene, ST18, as highly associated with the disease (Sarig et al, 2012;Vodo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Because the frequency of the rs2476601 T allele ( 1858T, 620Trp) was of only 1%–2% in Tunisians, the results did not permit exclusion of a possible effect of that PTPN22 variant on susceptibility to pemphigus in that population. Later, in a North American population, the frequency of the rs2476601 T allele was of 7.8% in both the pemphigus vulgaris patient and control samples, and no association was seen (Sachdev et al., ).…”
Section: Discussionmentioning
confidence: 99%